The Influence of Tangram Media on Students’ Learning Interest in Flat Shapes Material at MI Siti Mariam - Shalihah, Siti; Sarah, Siti (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2024)
This research aims to determine students' interest in learning in mathematics lessons on plane figures in class 2 MI Siti Mariam and to determine the influence of using Tangram media on students' interest in learning in mathematics lessons on plane figures in class 2 MI Siti Mariam. This research uses experimental research methods with a quantitative approach. Data collection using questionnaires, observations and interviews. The data analysis techniques used are normality test, homogeneity test and t-test. Based on the analysis carried out with the help of SPSS version 22, it was found that class 2 students' interest in learning mathematics regarding plane figures was in the category of very interested, 25%, 21.43% interested, 35.73% less interested, and 17.86% not interested. Apart from that, the results of the t-test were obtained with a calculated t-value of 15.628 and the significance level was 0.05, so the t-table value was 2.01537. So the value of t-count > t-table is 15.628 > 2.01537, so it can be concluded that there is a significant influence of the use of Tangram media on students' interest in learning in mathematics lessons about flat shapes in class 2 at MI Siti Mariam